ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS PENGUNGKAPAN SUSTAINABILITY REPORT - Tasya Karindra (2021)
This study is a quantitative study that aims to analyze the factors that influence the quality of sustainability report disclosure in companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This study uses secondary data in the form of sustainability reports and company annual reports. The sample of this study is 36 companies. Hypothesis testing in this study is using Multiple Linear Regression Analysis with SPSS program. The results of data analysis indicate that (1) environmentally sensitive industries has a positive and significant effect on the quality of sustainability report disclosure, (2) customer proximity industries has a positive and significant effect on the quality of sustainability report disclosures, (3) employee-oriented industries has no significant effect on the quality of sustainability report disclosures, (4) ownership concentration has no significant effect on the quality of sustainability report disclosure, (5) firm size as a control variable has a negative and significant effect on the quality of sustainability report disclosure while leverage, company age, and profitability have no significant effect on the quality of sustainability report disclosure.